Re-indução da tolerância à dessecação em sementes germinadas de feijão-caupi (Vigna unguiculata )L. (Walp.)) - Silva, Alexandre Carneiro da [UNESP] (2015)
The re-induction of desiccation tolerance (DT) in seeds consists in the treatment of germinated seeds, which are desiccation sensitive, in osmotic solutions to re-induce DT. The objectives of this work were to re-induce DT in germinated cowpea seeds, and to perform physiological, cytogenetic and ultrastructural studies in their primary roots aiming at understanding the mechanisms associated with the re-induction of DT. For the re-induction of DT, germinated seeds with 1, 2, 3 and 4 mm in primary root length were treated with a -1.7 MPa polyethylene glycol solution at 10°C, for periods of 0, 24, 48 and 72 hours. After this treatment, the seeds were dried for 3 days and rehydrated. Seeds that survived drying were considered DT. Treated and untreated seeds with primary roots lengths of 1, 2, 3 and 4 mm had their procambium cells evaluated for mitotic events and mitotic index. Also, an ultrastructural analysis was performed in the procambium region of radicles of seeds not imbibed, and in the primary root (2 mm length) of germinated seeds without drying and submitted to drying, and of the primary root from seeds germinated in water and subsequently treated with a -1.7 MPa polyethyleneglycol solution at temperature of 10°C for 24 hours without drying and subjected to drying. Finally, we quantified the contents of glucose, sucrose and raffinose in radicles of seeds not imbibed and imbibed in water for 16 hours, and in 2 mm length primary roots of germinated seeds treated (-1,7 MPa at 10°C for 8, 16 and 24 hours) and untreated. The treatment with osmotic solution of PEG at 10°C for 24 hours was efficient to re-induce DT in germinated seed of cowpea. The treatment with osmotic solution promoted the maintenance of the cell structures during desiccation and inhibited the cell cycle progress during the development of primary root of germinated seeds of cowpea, contributing to the re-induction of desiccation ...